Structural analysis of shearing mirror assembly in a lateral double-shearing interferometer - Li, Anhu; Luan, Zhu; Jiang, Xuchun; Bian, Yongming; Wang, Lijuan; Liu, Liren (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
By the finite element analysis method, the deformation and stress of the double-shearing mirror assembly is studied to validate the feasibility of the opto-mechanical structure. The side axial deformations (within Ø400 mm) of the upper semicircular mirror and the lower one are both up to micrometer order along the Y-direction under gravitational action. The equivalent stresses of two semicircular mirrors are more concentrated in the contact areas, but far less than the admissible stress of K9 material. The axial deformations of double-shearing mirror surfaces induced by the temperature rise are very serious, which are the major error sources for the measurement accuracy. The experimental results further validate the analysis conclusions available and show the opto-mechanical design to be reasonable.
Optica Applicata, Vol. 41, 2011, Nr 3, s. 701-715
Keywords: optyka; double-shearing mirror; gravitational action; thermoelastic deformation; finite element analysis; shearing interferometer